2018
DOI: 10.14740/jocmr3284w
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of Toxoplasma gondii Infection in Women of Reproductive Age: A Cross-Sectional Study in a Northwestern Mexican City

Abstract: BackgroundThrough a cross-sectional survey, we determined the seroprevalence and correlates of Toxoplasma gondii (T. gondii) infection in women of reproductive age in Hermosillo City, Mexico.MethodsWe studied 445 women of reproductive age in Hermosillo City in the northwestern Mexican state of Sonora. Women were enrolled in the University of Sonora. Sera of women were examined for IgG and IgM antibodies to T. gondii by commercially available enzyme immunoassays. The association of T. gondii seropositivity with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
(33 reference statements)
0
4
1
Order By: Relevance
“…The seroprevalence found in the present study is similar to T. gondii seroprevalences reported in pregnant women in other northern Mexican cities including Durango (6.1%), 10 and Aguascalientes (6.2%) 13 and women at reproductive age in the northwestern Mexican city of Hermosillo, Sonora (3.6%). 12 On the other hand, the seroprevalence of T. gondii infection found in the present study is lower than the 8.2% seroprevalence of this infection found in pregnant women in rural Durango State. 11 These studies used the same immunoassay to detect anti-T. gondii IgG antibodies.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…The seroprevalence found in the present study is similar to T. gondii seroprevalences reported in pregnant women in other northern Mexican cities including Durango (6.1%), 10 and Aguascalientes (6.2%) 13 and women at reproductive age in the northwestern Mexican city of Hermosillo, Sonora (3.6%). 12 On the other hand, the seroprevalence of T. gondii infection found in the present study is lower than the 8.2% seroprevalence of this infection found in pregnant women in rural Durango State. 11 These studies used the same immunoassay to detect anti-T. gondii IgG antibodies.…”
Section: Discussioncontrasting
confidence: 83%
“…9 Whereas seroprevalences of 6.1% and 8.2% were found in pregnant women in the northern Mexican city of Durango, 10 and rural Durango, 11 respectively. Seroprevalences of 3.6% and 6.2% were found in women of reproductive age in the northwestern Mexican city of Hermosillo, 12 and in pregnant women in the central Mexican city of Aguascalientes, 13 respectively. A summary of epidemiological data of previous studies of T. gondii infection in pregnant women in Mexico is shown in table 1.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 95%
“…Alvarado-Esquivel et al reported a similar finding. 29 These exposures to T. gondii could possibly be because of other risk factors like working with raw meat, which were not assessed in our study.…”
Section: Factors Associated With Seropositivitymentioning
confidence: 86%
“…23 The seroprevalence is the same as in Mexico, which has a similar arid climate. 29 A review of studies conducted in Africa found a median seroprevalence of T. gondii of 37%, with rates ranging from 6.4% to 74.5%. 12 Very little is known about the burden of CT in developing countries.…”
Section: Seroprevalence Of Anti-toxoplasma Gondii Iggmentioning
confidence: 99%
“…All the researches were narrowed into specified status like pregnancy and gyneco-obstetric problems. None of these fully included all categories of women of the childbearing age range (Rahman, et al [19][20][21][22][23][24][25][26][27][28][29][30][31]).…”
Section: Discussionmentioning
confidence: 99%